A simulation and analysis framework for CEE-eTOF. (1st July 2022) - Wang, B.; Chen, X.L.; Wang, Y.; Han, D.; Guo, B.
Abstract: This work reports the development status of a software framework for the external Time-Of-Flight wall (eTOF) of the Cooler-storage-ring External-target Experiment (CEE). The framework is implemented on CeeRoot, a FairRoot-based simulation and analysis platform. The chains for eTOF simulation and analysis have been developed and described in this paper. The examination of such a structure is in parallel with the technical design and prototype developments. Simulation has given reasonable evaluations on the coverage, occupancy, rate condition, etc., which validated the system design. The analysis chain has been successfully applied to processing the cosmic test data and has contributed to the validation of the prototype performances. The CEE-eTOF software is a continuously refining framework for practice in real operations.